Wound ballistics of firearm-related injuries—Part 2: Mechanisms of skeletal injury and characteristics of maxillofacial ballistic trauma. Issue 1 (January 2015) - Stefanopoulos, P.K.; Soupiou, O.T.; Pazarakiotis, V.C.; Filippakis, K.
Abstract Maxillofacial firearm-related injuries vary in extent and severity because of the characteristics and behaviour of the projectile(s), and the complexity of the anatomical structures involved, whereas the degree of tissue disruption is also affected by the distance of the shot. In low-energy injuries there is limited damage to the underlying skeleton, which usually dominates the clinical picture, dictating a more straightforward therapeutic approach. High-energy injuries are associated with extensive hard and soft tissue disruption, and are characterized by a surrounding zone of damaged tissue that is prone to progressive necrosis as a result of compromised blood supply and wound sepsis. Current treatment protocols for these injuries emphasize the importance of serial debridement for effective wound control while favouring early definitive reconstruction.